An in-situ Raman spectroscopic investigation in electric fatigue behaviors of PLZT ceramics. Issue 2 (1st February 2016) - Yang, Feng-Juan; Cheng, Xuan; Zhang, Ying
Abstract: A series of in-situ Raman spectra upon different polarization directions of incident and scattered lights ( θ ) and the corresponding hysteresis loops of unpoled lanthanum-doped lead zirconate titanate (PLZT) ceramics were simultaneously measured without and with applications of various electric fatigue cycle numbers ( N ). Accordingly, the relative Raman intensities in optical modes of E(2TO) over E(3TO+2LO)+B1 ( I E(2TO) / I E(3TO+2LO)+B1 ), the maximum changes in I E(2TO) / I E(3TO+2LO)+B1 at θ =0–360° (Δ R max ) and the remnant polarization ( P r ) were obtained for the as-received ( N =0) and differently electric fatigued ( N =10 0, 10 4, 10 5, 10 6 and 10 6.2 ) PLZT specimens. The characteristic electric fatigue behaviors observed for the unpoled PLZT ceramics were quantitatively analyzed by the normalized remnant polarization denoted as P r, N / P r, 10° and correlated to the average domain reorientation defined as Δ Rmax, N /Δ Rmax, 10° . It was concluded that during the electric fatigue process, the randomly orientated domains in the unpoled PLZT specimen as-received might be reoriented preferentially along the direction of the applied electric field initially. The electric fatigue reduced the extent of average domain orientation and significantly deteriorated the ferroelectric properties.